Nanoindentation and nanoscratching of iron: Atomistic simulation of dislocation generation and reactions - Gao, Yu (2014)
Using molecular-dynamics simulation, we study nanoindentation and scratching in an Fe (1 0 0) surface. We find an indentation hardness of 20 GPa in good agreement with experiment and previous simulations. The length of the dislocations generated and the volume of the plastic zone follow a simple model based on the dislocations necessary to remove the material from the indentation zone, the so-called geometrically necessary dislocations. The dislocation density stays approximately constant. Both b=1/2(111) and b=(100) dislocations contribute to the plastic zone. During scratching, we observe a distinct re-organization of the dislocation network; the reaction of b=1/2(111) to b=(100) dislocations plays an important role. After longer scratching the dislocations in the middle of the scratch groove react and the dislocation density there is strongly reduced; all further dislocation activity occurs at the scratch front. Deformation twinning is observed both in the indentation and in the scratch stage. Both normal and lateral scratch hardness decrease with depth, while the friction coefficient shows a strong increase.